1990
DOI: 10.1164/ajrccm/142.5.996
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Isoniazid-Rifampin Treatment for Pulmonary Tuberculosis in Children

Abstract: One hundred and seventeen children with pulmonary tuberculosis underwent treatment with a 6-month daily regimen of rifampin (15 mg/kg/day) and isoniazid (10 mg/kg/day). The criteria for the diagnosis of pulmonary tuberculosis were (1) clinical symptoms and signs in 93 children (79%), (2) history of direct contact with an adult with tuberculosis in 106 children (91%), (3) tuberculin reaction of 5 mm or more, without previous bacillus Calmette-Guérin (BCG), in 45 children (38%), (4) suggestive radiologic alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…102,168,169 With regard to children receiving only INH and RMP a number of authors commented on a reduced incidence of severe ADIH and jaundice, when the INH dosage was reduced to less than 15 mg/kg 99–101,168,169,192,196 or less than 10 mg/kg. 102 Amongst the 3 studies giving details of 224 children treated with only INH and RMP and receiving an INH dosage of approximately 8–15 mg/kg, only 2 (0.9%) children became jaundiced 99,174,175 compared to 52 (11.5%) of 453 children receiving INH in dosages of 10–20 mg/kg. 99,100,102,156,158,169,176 Turning to those studies where INH and RMP were combined with other agents, often including PZA, jaundice occurred in only 2 (0.07%) of 2714 children receiving RMP and INH in a dosage of approximately 10 mg/kg 13,79,80,94,157,161,177–185 and 5 (0.21%) of 2413 children receiving an INH dosage of 10–20 mg/kg, which does not suggest an influence of INH dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…102,168,169 With regard to children receiving only INH and RMP a number of authors commented on a reduced incidence of severe ADIH and jaundice, when the INH dosage was reduced to less than 15 mg/kg 99–101,168,169,192,196 or less than 10 mg/kg. 102 Amongst the 3 studies giving details of 224 children treated with only INH and RMP and receiving an INH dosage of approximately 8–15 mg/kg, only 2 (0.9%) children became jaundiced 99,174,175 compared to 52 (11.5%) of 453 children receiving INH in dosages of 10–20 mg/kg. 99,100,102,156,158,169,176 Turning to those studies where INH and RMP were combined with other agents, often including PZA, jaundice occurred in only 2 (0.07%) of 2714 children receiving RMP and INH in a dosage of approximately 10 mg/kg 13,79,80,94,157,161,177–185 and 5 (0.21%) of 2413 children receiving an INH dosage of 10–20 mg/kg, which does not suggest an influence of INH dosage.…”
Section: Discussionmentioning
confidence: 99%
“…169 Three papers give details of the management of children with INH 8–15 mg/kg and RMP. 99,174,175 All 224 children entered in these studies had AST and ALT regularly evaluated and 32 (14.3%) had increased values on at least one occasion. Two children (0.9%) became jaundiced 99 and three (1.3%) experienced symptoms compatible with ADIH.…”
Section: Hepatotoxicity Of Antituberculosis Agents In Children Treatementioning
confidence: 99%
“…Several controlled and observational trials of 6-month therapy in children with pulmonary TB caused by organisms known or presumed to be susceptible to the first-line drugs have been published [te Water Naude et al 2000;Tsakalidis et al 1992;Kumar et al 1990;Biddulph, 1990;Reis et al 1990;Jacobs and Abernathy, 1985;Varudkar, 1985;Al-Dossary et al 2002]. Although 6 months of therapy with isoniazid and rifampicin has been shown to be effective for treatment of hilar adenopathy and pulmonary TB, a threedrug regimen (isoniazid, rifampicin and pyrazinamide) has been shown to have success rates of greater than 95% and low adverse reaction rates.…”
Section: Tuberculosis Diseasementioning
confidence: 99%
“…72 However, over the past 2 decades, over a dozen studies and clinical trials of treatment of tuberculosis in children have been published. [73][74][75][76][77][78][79][80][81][82][83][84][85][86] These trials have shown that the basic regimen of 6 months of isoniazid and rifampin, supplemented during the first 2 months with pyrazinamide, cures over 99% of cases of drug-susceptible pulmonary tuberculosis in children, with an incidence of clinically significant adverse reactions of < 2%. Although a short period of daily administration of medications (the first 2-6 weeks) may be desirable, several studies have shown that giving two or three times per week intermittent treatment from the very beginning is effective in the vast majority of cases of pulmonary tuberculosis in children.…”
Section: Laboratory Evaluationmentioning
confidence: 99%